Gendered Fortunes Divination, Precarity, and Affect in Postsecular Turkey - Korkman, Zeynep K. (Duke University Press, 2023)
Zeynep K. Korkman examines Turkey's commercial fortune-telling cafes where secular Muslim women and LGBTIQ individuals can navigate the precarities of twenty-first-century life.